Penerapan Sistem Informatika di Sekolah Untuk Meningkatkan Efektivitas Pembelajaran - Safrial Safrial (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Informatics systems have an important role in improving the effectiveness of the learning process in schools. This study aims to analyze the effect of the application of informatics systems on the quality of learning. The research method used is an experimental study with a quantitative approach. Data were collected through observation, interviews, and questionnaires given to students and teachers. The results of the study indicate that the use of informatics systems, such as e-learning and technology-based academic management, can improve the efficiency of school administration and facilitate student access to learning materials. These findings indicate the importance of technology integration in the world of education.